The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11266-014-9526-2
|View full text |Cite
|
Sign up to set email alerts
|

Committed to Whom? Unraveling How Relational Job Design Influences Volunteers’ Turnover Intentions and Time Spent Volunteering

Abstract: This study presents a framework for understanding the processes through which volunteers' perception of relational job design influences their turnover intentions and time spent volunteering. Data sourced from an international aid and development agency in the United Kingdom (n = 534 volunteers) show that volunteers who perceive that their roles are relationally designed (1) report lower intentions to leave their voluntary organization due to their commitment to the voluntary organization; and (2) dedicate mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 61 publications
(85 reference statements)
5
26
1
Order By: Relevance
“…These include feelings that they had supported their local police force, were being treated fairly as a volunteer, were appreciated for the time they give and impact they made, were creating a difference in their community, and that their efforts as a volunteer were recognised. These findings resonate with those of Zhao et al (2012, p. 43 Vecina et al 2013, Alfres et al 2015. Stirling et al (2011) found that relational aspects of psychological contract relating to the volunteering ethos of trust, network and belonging were key features in shaping the success of volunteer management practices and influencing volunteer sustainability.…”
Section: Connection and Contributionsupporting
confidence: 87%
“…These include feelings that they had supported their local police force, were being treated fairly as a volunteer, were appreciated for the time they give and impact they made, were creating a difference in their community, and that their efforts as a volunteer were recognised. These findings resonate with those of Zhao et al (2012, p. 43 Vecina et al 2013, Alfres et al 2015. Stirling et al (2011) found that relational aspects of psychological contract relating to the volunteering ethos of trust, network and belonging were key features in shaping the success of volunteer management practices and influencing volunteer sustainability.…”
Section: Connection and Contributionsupporting
confidence: 87%
“…Aside from individual volunteer motives and dispositions, effective management within the organization also contributes to volunteer retention (Gazley, ; Hager & Brudney, ). Scholars have also examined volunteers' perceptions of the organizational context impacting retention success such as organizational climate (Nencini et al, ), the design of volunteer roles (Alfes, Shantz, & Saksida, ), organizational support (Alfes, Shantz, & Bailey, ), and job resources (Presti, ). Rather than relying on individual perceptions of volunteer management practices, this study builds on these findings and adopts a management perspective by drawing on objective measures of human resource (HR) practices that impact volunteer retention.…”
Section: Background and Significancementioning
confidence: 99%
“…Even though efforts have been made to develop a theoretical understanding of the potential for HR practices to impact volunteer retention, this research area remains underdeveloped (Alfes, Antunes, & Shantz, 2016) leading Bartram, Cavanagh, and Hoye (2017) to note that there is an "absence of research on the impact of HRM within volunteer and grassroots community organizations" (p. 1907-1908). As such, this study responds to calls for research on the impact of HR practices on volunteer outcomes (Alfes et al, 2015;Studer & von Schnurbein, 2013) by focusing on two prominent HR practices-training and recognition-and their impact on volunteer turnover. Particularly, we test the HR bundling perspective (Delery & Doty, 1996;MacDuffie, 1995) in the context of volunteers, indicating that HR practices work best if utilized in well-aligned bundles.…”
Section: Background and Significancementioning
confidence: 99%
“…Galindo-Kuhn and Guzley (2002) identified participation efficacy (volunteers' feelings that their participation will benefit someone) as a strong predictor of intent to remain volunteering. Alfes, Shantz and Saksida (2015) showed that the relational architecture of volunteer roles in an international development organization in the UK increased volunteers' intention to remain volunteering in the organization and was positively associated with the time dedicated to volunteering work.…”
Section: Opportunity-enhancing Hr Practicesmentioning
confidence: 99%